Development of Dual‐Pore Coexisting Branched Silica Nanoparticles for Efficient Gene–Chemo Cancer Therapy. Issue 7 (18th December 2017) - Lee, Jong‐Hwan; Kang, Seounghun; Ahn, Minchul; Jang, Hongje; Min, Dal‐Hee
Abstract: Various strategies for combination therapy to overcome current limitations in cancer therapy have been actively investigated. Among them, simultaneous delivery of multiple drugs is a subject of high interest due to anticipated synergistic effect, but there have been difficulties in designing and developing effective nanomaterials for this purpose. In this work, dual‐pore coexisting hybrid porous silica nanoparticles are developed through Volmer–Weber growth pathway for efficient co‐delivery of gene and anticancer drug. Based on the different pore sizes (2–3 and 40–45 nm) and surface modifications of the core and branch domains, loading and controlled release of gene and drug are achieved by appropriate strategies for each environment. With excellent loading capacity and low cytotoxicity of the present platform, the combinational cancer therapy is successfully demonstrated against human cervical cancer cell line. Through a series of quantitative analyses, the excellent gene–chemo combinational therapeutic efficiency is successfully demonstrated. It is expected that the present nanoparticle will be applicable to various biomedical fields that require co‐delivery of small molecule and nucleic acid. Abstract : Dual‐pore coexisting branched silica nanoparticles are simply synthesized by the Volmer–Weber growth pathway, which consists of a positively charged core with a large pore for nucleic acid loading and a negatively charged branched with small pore for small molecule loading. The platform shows features of efficient loading and controlled release, and represents synergetic anticancer effect through gene–chemo therapy.